Soft fragmentation of carbon monoxide by slow highly charged ions - Wells, E.; Nishide, T.; Tawara, H.; Watson, R. L.; Carnes, K. D.; Ben-Itzhak, I. (My University, 2008)
The fragmentation pattern and corresponding kinetic energy release distributions from carbon monoxide after collisions with slow, highly charged ions (C6+ at v=0.8 a.u. and Ar11+ at v=0.39 a.u.) are reported. Correlated measurements of the projectile final charge state and all charged molecular fragments were obtained using a coincidence time-of-flight technique coupled to projectile charge state separation. Fragmentation branching ratios for the dominant electron capture processes in these collisions are similar to those resulting from ionization by fast highly charged projectiles. This result can help simplify simulations of astrophysical or artificial plasma environments, as the branching ratio may be considered essentially constant for both electron capture and ionization as long as the relevant impact parameter is large.